2005
DOI: 10.1104/pp.105.070995
|View full text |Cite
|
Sign up to set email alerts
|

Double Knockouts of Phospholipases Dζ1 and Dζ2 in Arabidopsis Affect Root Elongation during Phosphate-Limited Growth But Do Not Affect Root Hair Patterning

Abstract: (M.L., X.W.)Root elongation and root hair formation are important in nutrient absorption. We found that two Arabidopsis (Arabidopsis thaliana) phospholipase Ds (PLDs), PLDz1 and PLDz2, were involved in root elongation during phosphate limitation. PLDz1 and PLDz2 are structurally different from the majority of plant PLDs by having phox and pleckstrin homology domains. Both PLDzs were expressed more in roots than in other tissues. It was reported previously that inducible suppression or inducible overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(179 citation statements)
references
References 25 publications
3
174
1
Order By: Relevance
“…In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig. 5; Nakamura et al, 2005;Li et al, 2006;Cheng et al, 2011), even if GDPD2 and 5 were only moderately induced. PLDz1 and PAH2 did not respond to Pi deficiency, and PAH1 was moderately (yet consistently) induced in the absence of Pi.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedsupporting
confidence: 66%
See 2 more Smart Citations
“…In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig. 5; Nakamura et al, 2005;Li et al, 2006;Cheng et al, 2011), even if GDPD2 and 5 were only moderately induced. PLDz1 and PAH2 did not respond to Pi deficiency, and PAH1 was moderately (yet consistently) induced in the absence of Pi.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedsupporting
confidence: 66%
“…However, the double KO pldz1 pldz2 contradicted these results since it did not exhibit any root hair alteration (Li et al, 2006). These conflicting results resemble our attempts to reproduce the root hair phenotype described previously for ppspase1 mutants and suggest either that these phenotypes were fortuitous or that there could be another unidentified factor controlling the link between root hair formation and choline, PCho, or PtdCho contents.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Although PC is present in the outer membrane of the plastid envelope, the only known site of PC de novo biosynthesis is localised in the ER. A direct import of PC from ER, or an import of intermediates derived from endoplasmic reticulum PC, possibly DAG or phosphatidate, is therefore required for the synthesis of eukaryotic galactolipids However, the existence of a phospholipase D (PLDζ2) activated by phosphate deprivation [42,43], the accumulation of phosphatidate in the tgd1 mutant and the localization of TGD1 in the chloroplast inner envelope membrane [37] suggest that the transported molecule could be phosphatidate. To understand this latter scheme, the precise localization of the phosphatidic acid phosphatase (PAP) involved in the transformation of eukaryotic phosphatidate into DAG is crucial since part of the eukaryotic DAG is galactosylated by MGD1, the constitutive MGDG synthase that is present in the inner envelope membrane.…”
Section: Energy-dependent Translocasesmentioning
confidence: 99%
“…Among the twelve PLDs recorded in Arabidopsis, PLDz1 and PLDz2 are homologous to mammal PLDs and play a role in the formation of galactolipids induced by Pi deprivation [22,23]. Interestingly, PLDz2 has been shown to be also involved in root system architecture, auxin-dependent hypocotyl elongation and vesicle cycling [60,61]. PLDz1 has been localized in vesicles underlying the plasma membrane [62] and PLDz2 in the tonoplast [63], which suggests that they hydrolyze specific pools of phospholipids in the endomembrane system.…”
Section: Mode Of Action Of Phosphatidic Acid In Signalling Eventsmentioning
confidence: 99%